Design and Simulation of Single Input Double Output Coupled Inductor Boost Converter with Bisection Method for Independent Home Application - Sudiharto, Indhana; Rifadil, Mochammad Machmud; Romadhoni, Muhammad Fauzi; Milchan, Muhamad (Universitas Syiah Kuala, 2024)
This paper proposed a converter design that functions as a voltage booster, increasing the input voltage while supplying two load outputs from a single voltage input using only one switch. Known as a single input double output (SIDO) converter, it aims to enhance power efficieny. The bisection method is employed as an output voltage controller through pulse width modulation (PWM) to achieve an optimal voltage value, adjusted to meet the load requirements. The loads used for independent home applications include a 72 V/12 Ah battery and a 24 V/22 W water circulation pump. The output of the high voltage level acts as a battery charger while the output of the low voltage level serves as an energy supply for the water cir-culation pump. The two loads were chosen because they are widely used, aligning with the goal of realizing independent home applications. The simulation test results showed that the voltage output for battery charging in constant voltage mode was 80.6 V, with an error of 0.0515%, and the voltage output for the water circulation pump was 24 V, with an error of 0.33%.